The Negative Role of Silence in Akan Communication - Agyekum, K. (Issues in Intercultural Communication 1(2): 159-178, 2007)
This paper looks at the negative roles of silence in communication and argues that speech is needed for perfect communication. Silence does not augur well for good communicative social interaction. Silence is a conversational killer and must be avoided under certain contexts since it makes it difficult for participants to detect interlocutors’ intention. The paper uses a descriptive and analytical method to find out the negativity of silence in communicative interactions. We will look at various ethnographic contexts such as organisations, institutions, religious worship, and non-face-to-face communication (letters, e-mails etc.). The paper compares silence with talk and sees speech positively as a joint production and therapy, and silence as negative.
Keywords: Silence; Negative Silence; Indigenous concepts; Distancing; Speech therapy